2022
DOI: 10.1007/s40732-022-00527-9
|View full text |Cite
|
Sign up to set email alerts
|

Probability Discounting in College Students’ Willingness to Isolate During COVID-19: Implications for Behavior Analysis and Public Health

Abstract: The present study was a preliminary analysis of college students’ willingness to self-isolate and socially isolate during the COVID-19 pandemic analyzed through a probability discounting framework. Researchers developed a pandemic likelihood discounting task where willingness to isolate from others was measured in days as a function of the perceived probability of the escalation of a virus to pandemic levels. Experiment 1 was conducted immediately prior to the World Health Organization (WHO) declaring COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Finally, valuation can change due to the discounting rate. Different studies have demonstrated that the discounting rate of pandemic consequences or money can predict adherence (Belisle et al, 2022;Camargo et al, 2021;Harman, 2021).…”
Section: Behavior Analysis Frameworkmentioning
confidence: 99%
“…Finally, valuation can change due to the discounting rate. Different studies have demonstrated that the discounting rate of pandemic consequences or money can predict adherence (Belisle et al, 2022;Camargo et al, 2021;Harman, 2021).…”
Section: Behavior Analysis Frameworkmentioning
confidence: 99%